2014
DOI: 10.4085/1062-6050-49.1.09
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effectiveness of Psychological Strategies on Physiologic Markers: Evidence-Based Suggestions for Holistic Care of the Athlete

Abstract: Context: Current holistic rehabilitation blends both physical and psychological techniques. However, validation of the usefulness of psychological strategies is limited in the literature.Objective: To quantify the effects of psychological strategies on both physiologic (salivary cortisol) and subjective assessments of stress.Design: Randomized controlled clinical trial. Setting: Laboratory. Patients or Other Participants: A total of 97 college-aged students (age ¼ 20.65 6 4.38 years), most with little to no ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…This can be majorly attributed to the fact that salivary cortisol levels capture the current state whereas PSS14 or the K10 Distress scale used in our study captures perceived stress over a month-long period. Similar results are also observed in a large number of other studies which use PSS14 or PSS10 as a measure for psychological stress (Dawson et al, 2014; Manigault et al, 2018; Putterman and Linden, 2006), whereas the studies using immediate perceived stress measures such as Visual Analog Scale or Stress-O-meter tend to find a correlation between salivary cortisol and perceived stress measures (Chellew et al, 2015; Chong et al, 2017; Esch et al, 2007; Linnemann et al, 2015; Myint et al, 2011). Men in our study showed a decrease in both perceived stress score (PSS14) and distress score (K10) with progression of time.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This can be majorly attributed to the fact that salivary cortisol levels capture the current state whereas PSS14 or the K10 Distress scale used in our study captures perceived stress over a month-long period. Similar results are also observed in a large number of other studies which use PSS14 or PSS10 as a measure for psychological stress (Dawson et al, 2014; Manigault et al, 2018; Putterman and Linden, 2006), whereas the studies using immediate perceived stress measures such as Visual Analog Scale or Stress-O-meter tend to find a correlation between salivary cortisol and perceived stress measures (Chellew et al, 2015; Chong et al, 2017; Esch et al, 2007; Linnemann et al, 2015; Myint et al, 2011). Men in our study showed a decrease in both perceived stress score (PSS14) and distress score (K10) with progression of time.…”
Section: Discussionsupporting
confidence: 80%
“…We hypothesised that stress perception within-individuals would be associated with elevation in cortisol responses. We also anticipated differences in cortisol and perceived stress responses between men and women (similar to other findings by Austin et al, 2018; Dawson et al, 2014). We finally predicted a decrease in perceived as well as physiological stress response along the longitudinal scale as individuals were expected to adjust to the novel academic and social environment over time.…”
Section: Introductionsupporting
confidence: 71%
“…Participants’ perceived stress was assessed by the Stress-O-Meter (SOM) scale with score of 0 (None) to 10 (Maximal) at the beginning of the standardized debriefing [27, 28].…”
Section: Methodsmentioning
confidence: 99%
“…We considered stress assessment methods that were compatible with simulated team management of life-threatening events. Self-reporting of stress applies various scales: the Stress-O-Meter (SOM) [ 56 ] and the State-Trait Anxiety Inventory (STAI) [ 57 ], commonly used in simulation [ 29 , 58 ]. PSTD is detected by the Impact of Event Scale-Revised (IES-R) on the 7 th day after the event [ 59 , 60 ] and the Post-traumatic Check-List Scale (PCLS) 1 month later [ 61 ].…”
Section: Methods and Designmentioning
confidence: 99%